Методика та методи суспільно-географічного дослідження територіальної організації освітньо-виховного комплексу обласного регіону - Заячук, Оксана; Zayachuk, Oksana (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Однією з важливих методологічних проблем дослідження регіонального освітньо-виховного комплексу є необхідність його детального системно-структурного аналізу. Використання широкого спектру методів дослі- дження дало змогу зосередити увагу на ієрархічних елементах територіальної структури освітньо-виховного комплексу. У статті проаналізовано та узагальнено суспільно-географічні підходи до вивчення освітньо- виховного комплексу як складової частини суспільно-територіальної системи та поглиблено методичні основи дослідження. Запропоновано алгоритм дослідження освітньо-виховного комплексу регіонального рівня (шість етапів). Визначено підходи та принципи дослідження, підкреслено важливість регіоналізації сучасних територіальних освітньо-виховних систем для подальшого впровадження інновацій і пошуку оптимальних шляхів розвитку. Necessity of detailed systemic-structural analysis of regional educational-incentive complex represents an important methodological problem of its study. The use of wide specter of study methods allowed for concentration upon hierarchic elements of educational-incentive complex’s territorial structure. The present article deals with the analysis and generalization of social-geographic approaches to said complex study as a component of social-territorial system, and with deepening of methodical bases for said study. The algorithm for the study of regional-level educational-incentive complex was suggested. Preparatory stage presupposes goal and tasks setting. Second stage (resource-knowledge) would be devoted to collection and initial processing of statistical materials, and archives data analysis. Third stage (analytical) presupposes that educational-incentive complex development factors be explored and deeply analyzed. The next (synthetic) stage would emphasize on the study and the analysis of the complex’s functional-component and organizational structures. Fifth stage would substantiate separation of some elements of educational-incentive complex and their interlinks. The last, prognostic stage, would lay in elaboration of major directions to develop territorial organization of educational-incentive complex. Study approaches and principles are defined. The present study stresses the importance of regionalization of present-day territorial educational-incentive systems for further introduction of innovations and search for optimal ways of development.
Territorial Organization of Regional Educational Complex within Administrative Oblast: Methods of Social-Geographic Study
Keywords: освітньо-виховний комплекс; методи суспільно-географічного дослідження; територіальна організація; Чернівецька область; educational complex; methods of social-geographic study; territorial organization; Chernivtsi region